Effect of micromorphology on transport properties of Nb‐doped anatase TiO2 films: A transmission electron microscopy study. Issue 3 (20th February 2017) - Ogawa, Daisuke; Nakao, Shoichiro; Morikawa, Kazuo; Ebisawa, Mizue; Hirose, Yasushi; Hasegawa, Tetsuya
Abstract : We investigate the transport properties and micromorphology of polycrystalline Nb‐doped anatase TiO2 (TNO) transparent conductive films, as a function of working pressure ( p w ) during sputtering. The TNO films were crystallized from amorphous precursors sputter‐deposited on unheated glass substrates. The micromorphologies of the TNO films were observed using a transmission electron microscope. The film deposited at a high p w of 1 Pa showed an inhomogeneous micromorphology, and a substantially low Hall mobility ( μ H ) of 2.0 cm 2 V −1 s −1 . However, films deposited at a low p w of 0.75 and 0.5 Pa exhibited less inhomogeneity in the micromorphologies and a high μ H of 3.8 and 9.2 cm 2 V −1 s −1, respectively. These results indicate that the inhomogeneous micromorphology acts as an additional carrier scattering source. The p w dependence of the micromorphology demonstrates that the inhomogeneous micromorphology originates from density fluctuation rather than sputter damage. The working pressure ( p w ) of sputtering significantly affects the micromorphology and, thus, the Hall mobility ( μ H ) of Nb‐doped anatase TiO2 (TNO) transparent conductive thin films.